Dynamics of an Intraguild Predation Food Web Cooperation Model Under the Influence of Fear and Hunting - Alyaa Hussain Naser; Dahlia Khaled Bahlool (Computation)
This study examines the impact of fear effects and cooperative hunting strategies in the context of intraguild predation food webs. The presented model includes a shared prey species with logistic growth and assumes that both the intraguild prey and intraguild predator draw their sustenance from the same resource. Using a Lyapunov function enables the system’s global stability to be proven. The impacts of key parameters on system stability are determined through bifurcation analysis. Numerical simulations show that even slight increases in the intensity of fear have drastic impacts on intraguild prey populations and, at higher levels, populations may go extinct. In addition, shifts in the parameter of cooperative hunting have a profound impact on the survival of the intraguild prey.